The Impact of Foreign Direct Investment on Myanmar's Economic Growth and Financial Sector Development - Nguyễn, Dương; Kyaw, Aung; Soe, Hlaing (Journal Development Manecos, 2023)
The objective of this research is to investigate the effects of FDI on Myanmar’s development especially on manufacturing, service and infrastructure industries. The study adopts an explanatory quantitative research approach using Sectional data collected from reliable sources such as world bank and Directorate of Investment and Company Administration (DICA). The research methodology involves using regression analysis to assess the impact of FDI on the GDP growth, Pearson’s correlation analysis to measure the FDI’s correlation with employment and technology transfer as well as the use of Analysis of variance (ANOVA), whereby the economic performance sectors with FDI is compared to that of sectors without FDI. Estimations presented here show that FDI has positive effects on Myanmar’s economic growth, rising from 3%. 42% to 6. 85% post-FDI. New employment rates were also documented to have increased from 68. 2% to 73. 4%. Furthermore, the technology transfer also expanded significantly pointing to FDI as a means to build up Myanmar’s technological endowment. In light of the findings of the study, it is therefore argued that FDI has positively enhanced economic development but there is the need to redouble efforts in trying to address some of the key issues that FDI faces in the country like bureaucratic procedures and regulations.